Upaya Guru Sekolah Dasar meningkatkan Pemahaman Siswa pada Materi Kasih Sayang terhadap Sesama menggunakan Media Video Pembelajaran Power Point - Bitha Satria Leri; Irwan Satria (Jurnal Indonesia Pendidikan Profesi Guru, 2024)
Objective: This study aims to determine the extent of students' understanding of the material on "Affection for Others" through PowerPoint learning video media at SD Negeri 56 Central Bengkulu. Method: The research employed a Classroom Action Research (CAR) method conducted in 2023 at SD Negeri 56 Bengkulu Tengah. The participants were 15 fifth-grade students. Data collection was carried out using observation sheets and interviews. Student learning completeness scores were used as the basis for data analysis.  Result: Using PowerPoint learning videos in Islamic Religious Education significantly improved students' attention, activeness, motivation, discipline, and task performance. This improvement was evidenced by a progressive increase in students' test results from the preliminary stage to Cycle I and Cycle II and from qualitative data gathered through observations and interviews. Conclusion: PowerPoint learning video media effectively enhances students' understanding and engagement with the "Affection for Others" material in Islamic Religious Education. Repeated cycles of action and reflection contributed to the learning improvement. Contribution: This study proves that integrating multimedia, specifically PowerPoint videos, into religious education can foster better student engagement and academic outcomes. It offers practical implications for teachers seeking to improve learning effectiveness through interactive and visually supportive instructional tools.